SPAG6 promotes proliferation and drug resistance in B-ALL cells through the NF-κB/ TNF-α pathway - PAN Shirui; PAN Shirui; LUO Jie; LUO Jie (陆军军医大学学报)
Objective To elucidate the underlying mechanisms of sperm-associated antigen 6(SPAG6) in the proliferation and drug resistance of B-cell acute lymphoblastic leukemia (B-ALL). Methods A total of 56 B-ALL patients and 15 iron-deficiency anemia (IDA) patients admitted in the First Affiliated Hospital of Chongqing Medical University from January 2019 to December 2023 were recruited and served as the experimental and control groups, respectively.Bone marrow mononuclear cells (BMMNCs) were derived from the bone marrow tissues of the experimental group.According to the results of qRT-PCR for the expression of SPAG6 in the obtained BMMNCs, the B-ALL patients were stratified into newly-diagnosed (New-diag) group, complete remission (CR) group, minimal residual disease Possitive (MRD+) group, and relapse group.Lentiviral vectors were used to construct B-ALL cells with SPAG6 overexpression and knockdown.CCK-8 assay and methylcellulose-based colony formation experiment were employed to assess the survival, proliferation, and clonogenic potential of the cells with varying SPAG6 expression levels.After f B-ALL cells were treated with the chemotherapeutic drugs, daunorubicin (DNR) and methotrexate (MTX), CCK-8 assay, flow cytometry and Western blot analysis were applied to detect cell viability (drug sensitivity and IC50), cell apoptosis, and protein levels of apoptosis-related molecules Bax, Caspase-3 and Bcl-2, respectively.The mRNA-seq profiles of B-ALL patients were obtained from the TARGET database, and gene set enrichment analysis (GSEA) was conducted to explore SPAG6-associated signaling pathways, which were subsequently validated experimentally.After treatment with the NF-κB agonist Phorbol 12-myristate 13-acetate (PMA) and the antagonist BAY-11-7082, cell viability and sensitivity to chemotherapeutic drugs were assessed with CCK-8 assay, and the expression of pathway-related proteins NF-κB P65, p-NF-κB p65, IKBα, p-IKBα, TNF-α, and EPO was detected by Western blot analysis.A mouse xenograft tumor model was constructed in SPAG6-/+ knockdown mice to observe the effect of DNR on tumor growth and the expression of the NF-κB signaling pathway in the tumor tissues with immunohistochemical assay. Results The mRNA level of SPAG6 was significantly higher in the B-ALL patients (P < 0.05), and in the MRD group (P=0.001) and R group (P=0.003) than the CR group.SPAG6 overexpression and knockdown in B-ALL cells confirmed that SPAG6 promoted the proliferation (P < 0.05) and decreased the sensitivity to DNR and MTX (P < 0.05).SPAG6 resisted chemotherapy-induced apoptosis in B-ALL cells by down-regulating pro-apoptotic proteins Bax and Caspase-3(P < 0.05), and up-regulating the expression of anti-apoptotic protein Bcl-2(P < 0.05).GSEA analysis suggested that the NF-κB pathway was enriched in B-ALL cells, and our experiments confirmed that SPAG6 enhanced the chemoresistance of B-ALL cells to chemotherapy by activating the NF-κB/TNF-α pathway.In in vivo experiments, knocking SPAG6 down significantly reduced the volume of transplanted tumors (P < 0.05), and an additional decrease in tumor growth was observed in the DNR-combined treatment group (P < 0.05), with reduced levels of NF-κB P65 and p-IKBα by immunohistochemical assay. Conclusion SPAG6 promotes the proliferation of B-ALL cells and reduces their chemosensitivity via the NF-κB/TNF-α pathway, suggesting a close association of SPAG6 with the therapeutic outcomes and prognosis in B-ALL patients.